Citizen science : how ordinary people are changing the face of discovery - Cooper, Caren B. (Overlook Press, 2016)
Cites the essential contributions of millions of ordinary people who contribute to the scientific process by volunteering in cooperation with scientists to help collect and discover information, tracing the history of citizen scientists and how they are reshaping scientific awareness.- Resumé vydavatele
Includes index.
Keywords: vědecký výzkum; občanská angažovanost; spolupráce; věda a společnost; scientific research; community involvement; cooperation; science and society; občanská věda; elektronické knihy; příručky; electronic books; handbooks and manuals